Implementation of a Decision Support System for Interpretation of Laboratory Tests for Patients; Studies in Health Technology and Informatics; Vol. 221 : Transforming Healthcare with the Internet of Things - Kopanitsa G. D. Georgy Dmitrievich (2016, 2016)
Title screen